2015
DOI: 10.1111/jth.13160
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemorrhagic complications are associated with lower coated‐platelet levels in non‐lacunar brain infarction

Abstract: To cite this article: Prodan CI, Stoner JA, Dale GL. Acute hemorrhagic complications are associated with lower coated-platelet levels in nonlacunar brain infarction. J Thromb Haemost 2015; 13: 2233-9.Summary. Background: Coated platelets are procoagulant platelets observed upon dual agonist stimulation with collagen and thrombin. Coated-platelet levels are elevated in patients with non-lacunar ischemic stroke and decreased in patients with spontaneous intracerebral hemorrhage as compared with controls. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Specifically, coated‐platelet levels are increased in patients with non‐lacunar stroke, in particular in those with large‐artery atherosclerosis, and elevated levels (>40%) are associated with recurrent cerebral infarction . However, lower coated‐platelet levels were observed in non‐lacunar stroke patients with imaging evidence of early hemorrhagic transformation within the infarction area (mean 29.1%) and in those with the highest incidence of acute hemorrhagic complications occurring during their initial admission for stroke (<35.5%) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, coated‐platelet levels are increased in patients with non‐lacunar stroke, in particular in those with large‐artery atherosclerosis, and elevated levels (>40%) are associated with recurrent cerebral infarction . However, lower coated‐platelet levels were observed in non‐lacunar stroke patients with imaging evidence of early hemorrhagic transformation within the infarction area (mean 29.1%) and in those with the highest incidence of acute hemorrhagic complications occurring during their initial admission for stroke (<35.5%) …”
Section: Discussionmentioning
confidence: 99%
“…17,19 However, lower coated-platelet levels were observed in non-lacunar stroke patients with imaging evidence of early hemorrhagic transformation within the infarction area (mean 29.1%) 32 and in those with the highest incidence of acute hemorrhagic complications occurring during their initial admission for stroke (<35.5%). 39 In sharp contrast to ischemic stroke, lower levels of coated-platelets were reported in intracerebral hemorrhage, including an increased risk for mortality noted at levels < 27.5%, 40 in severe hemophilia patients with increased bleeding phenotype, 41 and in human and animal studies focused on bleeding diatheses. 37,42 Commonly obtained platelet data, including platelet count, MPV, and aggregation studies were not abnormal in patients or animals with bleeding diatheses, 37,42 suggesting a differential involvement of the procoagulant and aggregation properties of platelets.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…In our study, we observed a distinct independent platelet population in response to collagen stimulation, defined as our procoagulant platelet population. As mentioned, procoagulant platelets such as coated platelets have been investigated mainly in brain infarction and intracranial haemorrhage, in which low CP levels are associated with microbleeds and acute haemorrhagic complications in nonlacunar stroke [12,33] and bleeding volume in patients with spontaneous intracerebral haemorrhage [13]. In patients with essential thrombocythemia, nontreated patients have lower coated platelet levels than hydroxyurea-treated patients and controls, which could be a contributing factor in essential thrombocythemia platelet dysfunction [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that all these different subpopulations form a spectrum of a single procoagulant platelet type [10,11] and it is recognized that collagen is the single most important agonist in the formation of procoagulant platelets [10]. Clinical investigations of procoagulant platelets pertain almost exclusively to coated platelets, which have been investigated in conditions such as stroke, spontaneous intracerebral haemorrhage, essential thrombocythemia, diabetes mellitus, Alzheimer's disease, haemophilia and bleeding diathesis [12][13][14][15][16][17][18]; however, for other procoagulant platelet subpopulations, clinical data are very limited and more data are needed to establish the clinical importance of procoagulant platelets.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, after the demonstration of a procoagulant platelet being predictive of bleeding or ischemic complications in patients with coronary artery disease, brain hemorrhage, traumatic brain injury, stroke, etc. [35][36][37][38][39][40][41][42] it is gaining more and more recognition. The importance of this subpopulation is further highlighted on a novel ex vivo model (which integrates all the core components of hemostasis [43]), where pharmacologic inhibition of platelet transition to a procoagulant state without affecting pro-aggregatory phenotype results in a decreased thrombus stability [44].…”
Section: Functions Of Procoagulant Plateletsmentioning
confidence: 99%